The comparison of Islamic banks performance in Indonesia before and after the Action to Defend Islam event - Luksi Visita (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2020)
Purpose – This study aims to compare the performance of Islamic banking before and after the Islamic defense action. The action to defend Islam is a manifestation of populism, which resulted in mixed responses.Method – Financial performance consisting of return on assets (ROA), financing to deposit ratio (FDR), third party funds (DPK), non performing financing (NPF) and profit sharing financing on total financing were analyzed from 30 Islamic commercial banks and Sharia business units in Indonesia. The data were analyzed using different test paired sample T-test.Result – The results show that only TPF and FDR have significant differences. The DPK value increases, while the FDR decreases.Implication – This study can support industry to consider aspects needed to be taken care of during political events.Originality – This study enriches the empirical study of political and business interaction.